INTERCULTURAL INTERACTION OF FOLK-STAGE DANCE OF UKRAINE AND EUROPEAN COUNTRIES - Volchukova, Viktoriia; Tishchenko, Olena (The Modern Higher Education Review, 2023)
In the current stage of development of Ukraine, during martial law, the problem of strengthening intercultural interaction between different peoples of the world acquires special significance. A significant issue in intercultural interaction between Ukraine and Europe today is the rapprochement of ethnic cultures and the assimilation of cultural and moral values, customs, and dance traditions. In Ukraine, strengthening intercultural interaction between peoples is one of the key factors of peace and interethnic harmony. International folk dance festivals, where you can see folk dances from around the world, play a significant role in creating intercultural interaction and ensuring dialogue between the Ukrainian people and European countries. These festivals ensure the exchange of dance traditions, customs, highly artistic repertoire, and stage culture from different countries of the world. The article is aimed at studying the features of intercultural interaction of folk stage choreography of the Volyn and Bukovinian regions of Ukraine and European countries: Hungary, Slovakia, Moldova, Romania and Poland, in particular, determining the mutual influence of regional features of dance vocabulary and folk dance forms of these countries. The article is intended for future teachers of choreographers, teachers of choreographic disciplines and leaders of choreographic groups, who must be ready to create a highly artistic dance repertoire and master the methods of teaching folk dances from around the world, know the features of their dance vocabulary, forms and genres of choreographers.